Taxation of Shareholder Income and the Cost of Capital in a Small Open Economy - Peter Birch Sørensen (Center for Economic Studies and ifo Institute (CESifo), 2014)
When companies finance their investment via the international markets for stocks and bonds, relief from domestic personal taxes on dividends and capital gains will not reduce the cost of capital. Some authors have shown that even for small domestic companies whose shares are not traded internationally, domestic shareholder tax relief will not necessarily reduce the cost of equity finance. This paper argues that, under realistic assumptions, domestic shareholder tax relief will in fact reduce the cost of capital for small firms. It also argues that a shareholder income tax on the equity premium with full loss offset will improve the allocation of risk in the economy.
Keywords: H20; 330; double tax relief; cost of capital; dividend taxation